MO431LIPIDOMIC ANALYSIS IN A NON-DIABETIC RAT MODEL WITH HYPERFILTRATION AND ALBUMINURIA REVEALS DYNAMIC CHANGES IN THE PROSTAGLANDIN E2 PATHWAY DURING ONSET OF ALBUMINURIA AS A POTENTIAL CAUSATIVE MECHANISM. (29th May 2021) - Mangelsen, Eva; Rothe, Michael; Bolbrinker, Juliane; Kourpa, Aikaterini; Panáková, Daniela; Kreutz, Reinhold; Schulz, Angela Martina
Abstract: Background and Aims: We recently identified prostaglandin reductase 2 ( Ptgr2 ) and the prostaglandin E2 (PGE2) pathway as potential causative mechanism in the Munich Wistar Frömter (MWF) non-diabetic rat model of chronic kidney disease. MWF is characterized by early onset of spontaneous albuminuria during a critical time window between 4 and 8 weeks of age, that associates with hyperfiltration, due to low nephron number, and podocyte injury. Ptgr2 plays an important role in the prostaglandin metabolism, in which PGE2 is metabolized by 15-prostaglandin dehydrogenase (15-PGDH) to 15-keto-PGE2. The latter is terminally degraded by prostaglandin reductases (PTGRs) 1, 2, and 3 to 13, 14-dihydro-15-keto-PGE2. Recently, we detected elevated glomerular levels of PGE2 and 15-keto-PGE2 in MWF compared to spontaneously hypertensive rats (SHR) with no albuminuria. The aim of the present study was to characterize in detail the renal PGE2 metabolic pathway in MWF by lipidomic analysis during the time window of albuminuria onset. Method: Male MWF and SHR rats were studied at week 4 and 8, respectively; 24 h-urine was collected in metabolic cages. In addition, plasma and kidney tissues including kidney cortex and isolated glomeruli were obtained from anesthetized rats. Lipidomic analysis was done by liquid chromatography electrospray ionization tandem mass spectrometry. Statistical analysis was performed by unpaired, two-tailed Student's t-test, or otherwise the Mann-Whitney test. Results: Urinary PGE2 was significantly lower (p<0.01), while urinary 15-keto-PGE2 and 13, 14-dihydro-15-keto PGE2 levels were significantly increased in MWF compared to SHR at week 4 (p<0.01, respectively). All three analytes were significantly decreased in urine of MWF with increased albuminuria at week 8 (p<0.05 vs. SHR). The urinary metabolic ratio of 15-keto-PGE2/13, 14-dihydro-15-keto-PGE2 as a surrogate for PTGRs activities was significantly increased at week 4 (p<0.01), whereas it was significantly decreased in MWF vs. SHR at week 8 (p<0.05). Plasma levels of PGE2 and 13, 14-dihydro-15-keto-PGE2 did not differ between strains at both time points, while 15-keto-PGE2 was below the detection limit. Glomerular levels of PGE2 and 15-keto-PGE2 were increased in MWF at week 4 and 8 (p<0.01, respectively). In contrast, 13, 14-dihydro-15-keto-PGE2 was only significantly higher at week 4 compared to SHR (p<0.01). In isolated glomeruli, the metabolic ratios of PTGRs were similar between the strains at week 4, but significantly increased in MWF compared to SHR at week 8 (p<0.01, respectively). In kidney cortex, 15-keto-PGE2 and 13, 14-dihydro-15-keto-PGE2 were increased in MWF at week 4 (p<0.05 and p<0.01, respectively), whereas PGE2 levels were comparable to SHR. No difference for cortical levels of PGE2 and its metabolites was observed at week 8. Conclusion: This study provides the first insights into age-dependent dynamic changes in the PGE2 pathway that support potential causality for the onset of albuminuria in the setting of non-diabetic hyperfiltration due to low nephron number. Notably, the increased glomerular levels of PGE2 and its downstream metabolites in 4-week-old MWF point towards an early activation of this pathway, i.e. before albuminuria occurs. This finding corroborates the hypothesis that glomerular PGE2 signaling is relevant in the early stages of hyperfiltration and suggests this pathway as a target for future therapeutics to modify the manifestation and progression of renal disease.